THE ROLE OF PERSONNEL IN ENSURING THE CYBERSECURITY OF CRITICALLY IMPORTANT INFRASTRUCTURE OF UKRAINE - Pidlisna, T. V. (The actual problems of regional economy development, 2024)
The research aims to study strategies for enhancing the role of personnel in cybersecurity within organizational settings. The main objective is to identify the most effective approaches to ensure active participation of personnel in defending against cyber threats and maintaining cybersecurity in organizations. The study is based on the analysis of literature sources, including scholarly articles, materials, reports, and practical case studies. Synthesis and analysis methods are applied to determine strategies and practical recommendations for organizations. The research identified a range of strategies for enhancing the role of personnel in cybersecurity, including comprehensive training and awareness raising, fostering a culture of security, defining clear roles and responsibilities, promoting cross-functional collaboration, and providing recognition and incentives. These results have practical significance for implementation in organizations. The research offers an original perspective on cybersecurity through the active participation of personnel in organizations and considers strategies that can be applied to enhance the effectiveness of cybersecurity measures. The recommendations and conclusions of the study have practical significance for organizations seeking to strengthen their cybersecurity and maximize internal resources for protection against cyber threats. Key findings of the research emphasize the importance of personnel as a critical component of cybersecurity strategies. Personnel serve as the first line of defense against cyber threats, acting as a "human firewall" to detect, prevent, and respond to potential security incidents. By promoting a security-conscious mindset among personnel, organizations can significantly reduce the likelihood of successful cyber-attacks and minimize the impact of security breaches. The study also highlights the necessity of comprehensive training programs, continuous education, and awareness campaigns to equip personnel with the knowledge and skills required to recognize and mitigate cyber risks. Additionally, the research underscores the importance of clear roles and responsibilities, cross-functional collaboration, and incentivizing cybersecurity efforts to foster a culture of security awareness and proactive defense. The research provides a detailed analysis of case studies from various organizations that have successfully implemented cybersecurity initiatives. These case studies offer valuable insights into effective practices, including the establishment of Incident Response Teams (IRT), the implementation of security awareness training programs, and proactive insider threat mitigation strategies. By examining these real-world examples, organizations can gain practical guidance on enhancing their cybersecurity posture and resilience against evolving cyber threats. The research emphasizes that the active involvement of personnel is crucial for the effective implementation and maintenance of cybersecurity measures within organizations. By investing in personnel training, fostering a culture of security awareness, and promoting collaboration, organizations can enhance their ability to defend against cyber threats and safeguard their critical infrastructure. The findings and recommendations of this study are intended to provide practical insights and strategies for organizations aiming to strengthen their cybersecurity defenses and maximize their internal resources for effective protection against cyber threats.